A Phase Ib Study of Single‐Agent Idelalisib Followed by Idelalisib in Combination with Chemotherapy in Patients with Metastatic Pancreatic Ductal Adenocarcinoma. (18th June 2020) - Borazanci, Erkut; Pishvaian, Michael J.; Nemunaitis, John; Weekes, Colin; Huang, Julie; Rajakumaraswamy, Nishanthan
Abstract: Trial Information: ClinicalTrials.gov  Identifier:  NCT02468557 Sponsor: Gilead Sciences, Inc. Principal Investigators: Erkut Borazanci IRB Approved: Yes Lessons Learned : Although this study of idelalisib in patients with PDAC was limited in size and duration because of early termination, idelalisib exposure resulted in an overall safety profile consistent with studies in hematological malignancies, except that the incidences of diarrhea and colitis were reduced in patients with PDAC. Preclinical studies of the PI3K pathway in PDAC and positive clinical results of PI3K inhibition in other cancers support the continued development of PI3K inhibitors in PDAC. Background: Pancreatic ductal adenocarcinoma (PDAC) is among the most lethal solid tumors and is often refractory to treatment. Phosphatidylinositol‐3 kinase (PI3K) δ inhibition influences regulatory immune cell function and improves survival in preclinical PDAC models. Here, idelalisib, an inhibitor of PI3Kδ, was investigated as treatment for metastatic PDAC. Methods: This was an open‐label, multicenter, phase Ib, nonrandomized, dose‐escalation study. Study aims were to investigate the maximum tolerated dose, safety, pharmacokinetics/pharmacodynamics, and efficacy of idelalisib alone and in combination with chemotherapeutics—nab‐paclitaxel and modified (m)FOLFOX6. Results: Because of early termination, only 16 patients were enrolled in the single‐agent idelalisib arm, 12 of whom received at least one dose of idelalisib. The most common treatment‐emergent adverse events (≥25%) related to idelalisib ( n = 12) were increased aspartate aminotransferase, pyrexia, and maculopapular rash. One patient presented with diarrhea; no cases of colitis were reported. One patient discontinued treatment because of pyrexia and maculopapular rash; two patients died because of disease progression. Conclusion: This study was terminated because factors contributing to safety concerns in phase III studies of idelalisib for hematological malignancies were not fully understood. In this small sample of patients with metastatic PDAC, exposure to idelalisib resulted in safety findings consistent with previous studies, with reduced diarrhea/colitis.